Storytelling Globalization from the Chaco and Beyond - Blaser, Mario (New Ecologies for the Twenty-First Century, 2010)
For more than fifteen years, Mario Blaser has been involved with the Yshiro people of the Paraguayan Chaco as they have sought to maintain their world in the face of conservation and development programs promoted by the state and various nongovernmental organizations. In this ethnography of the encounter between modernizing visions of development, the place-based "life projects" of the Yshiro, and the agendas of scholars and activists, Blaser argues for an understanding of the political mobilization of the Yshiro and other indigenous peoples as part of a struggle to make the global age hospitable to a "pluriverse" containing multiple worlds or realities. As he explains, most knowledge about the Yshiro produced by non-indigenous "experts" has been based on modern Cartesian dualisms separating subject and object, mind and body, and nature and culture. Such thinking differs profoundly from the relational ontology enacted by the Yshiro and other indigenous peoples. Attentive to people's unique experiences of place and self, the Yshiro reject universal knowledge claims, unlike Western modernity, which assumes the existence of a universal reality and refuses the existence of other ontologies or realities. In Storytelling Globalization from the Chaco and Beyond, Blaser engages in storytelling as a knowledge practice grounded in a relational ontology and attuned to the ongoing struggle for a pluriversal globality